Psychometric evaluation of nursing interns' consciousness of rights scale in clinical practice - Yuting Zeng; Hongyu Li (BMC, 2023)
Abstract Objective The purpose of this study was to translate the Awareness of Rights Scale into Chinese and test its psychometric properties among nursing students in clinical practice. Methods The original English scale was translated, synthesized, and back-translated according to the Brislin translation model: the translated scale was cross-culturally adapted through expert correspondence and pretesting to form the Chinese version of the scale; a convenience sampling method was used to survey 486 nursing interns in Liaoning, Guangdong, and Anhui regions to assess the reliability and validity of the scale. Results The Chinese version of the scale consists of 14 items in three dimensions. The Cronbach's alpha value of the scale was 0.916 and the range of Cronbach's alpha coefficients of subscale was 0.768 to 0.894. The discounted half reliability was 0.867 and the retest reliability was 0.901. The scale content validity index (S-CVI) was 0.963. A total of three common factors were extracted for the exploratory factor analysis. The confirmatory factor analysis indices fit well (χ2/df = 1.092, RMSEA = 0.014, CFI = 0.998, IFI = 0.998. TLI = 0.997), and the model fit was good. Conclusion The Chinese version of the scale has good reliability and validity in the nursing intern population and can be used to assess nursing interns' awareness of their rights in clinical practice in mainland China.